2022
DOI: 10.3390/machines10050290
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Novel Fully Automated Concept to Produce Bowden Cables for the Automotive Industry

Abstract: The automotive industry is one of the driving forces of the global industry; thus, it is a very competitive sector which creates a constant need for process improvement, regarding productivity, quality, and flexibility. Automation has proven to be a viable solution for these production problems, with the rising adoption of these automated system by companies that try to design and implement more flexible systems, while reducing costs and improving process quality. Furthermore, the use of automation reduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…All devices that directly interfered with the productivity of the equipment and that were not able to satisfy the new requirements were replaced or improved. As in works previously presented by other authors [34,[42][43][44]46,47,[65][66][67], the choice to solve the problems identified essentially involved the adoption of conventional automation driven by programmable devices, to the detriment of robotics, despite initially considering the use of robotics. In fact, for situations such as the case under study, where competitiveness and a quick return on investment are crucial factors for the adoption of the developed concepts, conventional automation usually represents a more economical solution that consumes less area on the shopfloor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All devices that directly interfered with the productivity of the equipment and that were not able to satisfy the new requirements were replaced or improved. As in works previously presented by other authors [34,[42][43][44]46,47,[65][66][67], the choice to solve the problems identified essentially involved the adoption of conventional automation driven by programmable devices, to the detriment of robotics, despite initially considering the use of robotics. In fact, for situations such as the case under study, where competitiveness and a quick return on investment are crucial factors for the adoption of the developed concepts, conventional automation usually represents a more economical solution that consumes less area on the shopfloor.…”
Section: Discussionmentioning
confidence: 99%
“…However, this concept was not yet complete, as the equipment was not capable of automatically performing the second injection of Zamak, which ends the cable, after it is essentially complete. Thus, Sousa et al [44] developed a new concept that extended the capabilities of the previously developed equipment, allowing, in the same sequence, the equipment to include a second Zamak injection machine, which allowed the closure of the production cycle and defined the cable as complete. This study made it possible to proceed with the complete integration of all processes inherent in the production of Bowden cables, eliminating intermediate stock and logistical operations that did not add any value.…”
Section: State Of the Artmentioning
confidence: 99%
“…The automatic machine developed in this work for spiral double-cutting followed the design science research (DSR) methodology. This approach is particularly suited for the design and improvement of existing processes, as in the current work, and it involves the detailed study of the existing processes and proposal of new solutions arising from the inputs of different participants in the process, leading to an improvement process that can be used in different disciplines [3]. The DSR methodology is step forward compared to traditional design, in which the interested parties (companies) define the objectives and requirements in a short-term perspective, limited by the available knowledge and productions resources.…”
Section: Selected Methodologymentioning
confidence: 99%
“…These functions vary from safety to comfort equipment. Applications of control cables are found in many fields of engineering such as robotics [2], and the automotive industry represents one of the most common and generalized applications [3]. Control cables, also known as Bowden cables, transmit linear motion and power by the relative displacement of cable or wire inside a spiral.…”
Section: Introductionmentioning
confidence: 99%
“…Automation can be as simple as a thermostat regulating room temperature or as complex as a fully automated assembly line [6]. The primary goal is to enhance efficiency and productivity while minimizing errors [7]. This approach has found its place in a variety of industries, with the automotive sector emerging as a major catalyst for the advancement of automation systems, driven by the pursuit of heightened productivity and enhanced flexibility [8,9].…”
mentioning
confidence: 99%